Analysis of farmers’ behaviour towards purchase of improved sweetpotato vines in Uganda: An application of the AIDA model - Otieno, D.J.; Rajendran, S.; Okello, J.J.; Ogero, K.; Feukeng, F. (2024)
Many studies on adoption of new technologies assume a linear movement from introduction of the technologies to their eventual uptake by targeted stakeholders. However, human behavior follows a gradual and cumulative path from information acquisition, developing an interest, forming a desire and eventually taking action to use new technologies. This study provides analytical results on how a farmer moves from being aware, getting interested, forming a purchase desire and actually purchasing improved sweetpotato seed in Uganda. The study uses primary data from both a baseline and follow up survey of 1192 sweetpotato farmers in Amuria district of Uganda. Principal component analysis and partial least square structural equation model were applied to analyze the empirical linkages between four key constructs; awareness, interest, desire and action (commonly referred to as AIDA model) in tracing the farmer’s journey towards eventual purchase and use/planting of the improved sweetpotato vines. Results show that contrary to theoretical expectation of a linear relationship and exact prediction of action from awareness, interest and desire, the baseline data only linked 47.6% of farmer behavior towards purchase of the improved sweetpotato vines to the sequential movement from awareness, interest and desire. Two distinct categories of farmers were also established; keen customers who pay attention to product details and environmentally-conscious customers who care more about product costs and adaptability to drought and low water stress. The follow up survey plus inclusion of contextual factors improved the explained variance from 48% in the baseline data to 60%. This implies that farmers’ behavior towards adoption of improved sweetpotato requires multiple rounds of data spread over a longer time period to correctly predict. Moreover, contextual factors such as farmers’ resource endowment situation, gender roles and culture add value to the standard AIDA model constructs and should be incorporated in such models to improve the precision of analysis and make the findings more relevant to farmers’ environment, thus resulting to realistic interventions.